Strategy of Islamic Financial Institutions in Improving Financial Access and Community Welfare: A Review of BMT Muamalat Limpung Batang Regency - Randhini Putri Amanda (Journal of Economic and Business Analysis, 2024)
Abstract: People's limited access to formal financial institutions leads to dependence on informal funding sources such as loan sharks. Islamic microfinance institutions such as Baitul Maal Wat Tamwil (BMT) have grown rapidly in the last 15 years to answer the needs of the community. BMT plays a role in improving community welfare through providing access to financing with sharia principles. This study examines BMT's strategy in improving financial access and community welfare by taking the case study of BMT Muamalat Limpung. BMT Muamalat applies mudharabah financing products with a profit sharing portion of 70:30 and 50:50. The target of financing is SMEs with assets of IDR 500,000 to IDR 60,000,000. BMT Muamalat offers a financing period of 1 to 4 months with a total financing of IDR 500,000 to IDR 60,000,000. This strategy aims to facilitate the working capital needs of SMEs in order to develop their business and improve welfare. The results showed that BMT plays a role in expanding financial access by reaching non-bankable communities and improving welfare through sharia-based SME financing. Keywords: BMT; sharia financing; mudharabah; financial access, community welfare